(untitled) (Estudos em Design, 2019)
RCA School of Communication Research Work in Progress Abstracts A diverse group of emerging communication researchers present their work-in-progress at Westworks in White City. Through a variety of activities – workshops, screenings, exhibits, talks, they will convey the intentions underlying their investigations, which are posited around three interconnected threads: conversation, experience and knowledge. Introduction by Teal Triggs Exhibitors Conversations Karen Bosy Sinead Evans Vicky Kim Hotessa Laurence Paul Ransom Welmoet Wartena Experiences Gesi An Farah Kadhum Paul DJ Moody Larissa Nowicki Simon Picard Kelly Spanou Rimjhim Surana Knowledge Wenbo Ai Mallaa Alamoudi Kollontai Cossich Diniz Fernando Galdon Emily Hoong Sarah Kirby-Ginns Cristina Portugal Patricia Puertas Caroline Ward